A aplicação do ensino de historia da ciência em uma aprendizagem significativa da disciplina Química - Santos Sobrinho, Celso Luis Soares dos (2010)
This thesis describes an application of the History of Science classes on weight laws in order to achieve a meaningful learning Chemistry as a subject. To do so, we used the maximum of available teaching resources and a socioeconomic questionnaire that when combined to evaluations would bring a parameter of the evolution of the research subjects in relation to the topics of the subject, providing a plausible analysis of the proposed situation. Also, an analysis of textbooks selected by PNLEM (National Program of Ensino Medio Books) was accomplished as well as an interview with a group of chemistry teachers from several institutions in order to recognize the level of relevance given to either to the History of Science in classes taught by this group and or to textbooks recommended by the Ministry of Education and Culture (MEC). This work aims also at stimulating learner’s ability for questioning and interpretating, which are considered basic skills to the constitution of citizens imbued with a critical sense.